1993
DOI: 10.1093/jn/123.4.656
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain of Kenyan School Children Infected with Hookworm, Trichuris trichiura and Ascaris lumbricoides is Improved Following Once- or Twice-Yearly Treatment with Albendazole

Abstract: We studied growth in infected children given one dose (600 mg) or two doses of albendazole per school year. Children were examined and allocated at random within sex by descending hookworm egg count to one of three groups: placebo (n = 93), one dose (1x, n = 96) or two doses (2x, n = 95). Each child was treated and then re-examined and treated 3.6 and 8.2 mo later (Exams 2 and 3). The 1x and 2x groups gained significantly more by Exam 3 than the placebo group in weight (1.1 and 0.9 kg more, respectively), perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
92
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(96 citation statements)
references
References 9 publications
3
92
1
Order By: Relevance
“…Others have found associations of infection with intake of ring-well water [19] and river water [14] which is inconsistent with what we found in our study. Probably, the hand pumps which are dug at the shallow level come in contact with raw sewage due to proximity with open drain/ canal, overflowing drains, physical contact with wastewater or with open defecation and public washing and thus provided optimum conditions for the survival and development of the eggs of Ascaris lumbricoides.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Others have found associations of infection with intake of ring-well water [19] and river water [14] which is inconsistent with what we found in our study. Probably, the hand pumps which are dug at the shallow level come in contact with raw sewage due to proximity with open drain/ canal, overflowing drains, physical contact with wastewater or with open defecation and public washing and thus provided optimum conditions for the survival and development of the eggs of Ascaris lumbricoides.…”
Section: Discussioncontrasting
confidence: 99%
“…A Keynesian study also found that households without soap had a 2.6 times higher risk of being infected with Ascaris lumbricoides compared with households where soap was available. [19] Since a majority of the respondents in Gyanpur (97.3%, n = 472) and Murhu blocks (97.1%, n = 454) in our study defecated in the open air, we could not estimate any association between field defecation and positivity of infection in either blocks.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The negative impact of parasitic infections on growth is observed in many studies that use different measurements and indicators of anthropometric status, such as weight [15][16][17][18] , height [19][20][21] weight-forage 16,22 , height-for-age 16 and weight-forheight 17,[22][23][24] . For these authors, infections act negatively over the genetic growth potential of children and adolescents, keeping them from reaching full somatic growth.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] High prevalences of intestinal parasites among local residents of East Africa have been documented by previous studies. Ascaris lumbricoides (26-35%), T. trichiura (79-92%), and hookworm (85-93%) infections are especially common among schoolchildren in the region, [28][29][30] and are known to contribute to malnutrition and developmental disabilities among infected children. [28][29][30][31] Based on the regional prevalence of helminths and prior to the enhanced health assessments, CDC recommended mass therapy for intestinal parasites with mebendazole (100 mg twice a day for 3 days).…”
Section: Discussionmentioning
confidence: 99%